Epitranscriptomic Control of Drought Tolerance in Rice: The Role of RNA Methylation - Xiaoru Fan; Yong Zhang; Pengyuan Gu; Misbah Naz (Plants, 2025)
Drought stress is a predominant abiotic constraint adversely affecting global rice (Oryza sativa) production and threatening food security. While the transcriptional and post-transcriptional regulation of drought-responsive pathways has been widely investigated, the emerging field of epitranscriptomics, particularly RNA chemical modifications such as N6-methyladenosine (m6A), adds a new dimension to gene regulation under stress. The most prevalent internal modification in eukaryotic messenger RNA influences RNA metabolism by interacting dynamically with enzymes that add, remove, or recognize the modification. Recent studies in rice reveal that m6A deposition is not static but dynamically regulated in response to water-deficit conditions, influencing transcript stability, splicing, nuclear export, and translation efficiency of key drought-responsive genes. This review critically synthesizes current findings on the distribution and functional implications of m6A and other epitranscriptomic marks (e.g., 5-methylcytosine [m5C], pseudouridine [Ψ]) in modulating rice responses to drought. We discuss the regulatory circuitry involving m6A effectors such as OsMTA, OsFIP37, and YTH domain proteins and their integration with known drought-signaling pathways including ABA and reactive oxygen species (ROS) cascades. We also highlight emerging high-resolution technologies such as m6A-seq, direct RNA sequencing, and nanopore-based detection that facilitate epitranscriptomic profiling in rice. Finally, we propose future directions for translating epitranscriptomic knowledge into crop improvement, including CRISPR/Cas-based modulation of RNA modification machinery to enhance drought tolerance.